Kajian Gua Umang Tanjung Pulo dalam Konteks Folklor dan Budaya Lokal - Hidayati, Dyah; Hidayat; Amal, Bakhrul Khair (PURBAWIDYA, 2025)
Folklore is one of the cultural products that often underlie the existence of an archaeological site, one of which is the Umang folklore that frames the archaeological site of the Umang Cave in Tanjung Pulo, Tiganderket District, Karo Regency, North Sumatra Province. This study aims to descriptively outline the archaeological aspects of Umang cave tanjung pulo, the folklore that forms the background story of the cave’s existance, as well as the relationship between the two. The methods used include observation (object description, measurement, documentation, and environmental observation); an ethnographic approach through interviews, and literature review. The result of this research are: the umang folklore that developed among the Karo people is part of the Nusantara folklore. Specifically in Sumatera, such supernatural beings are generally known as bunian. The Umang Cave in Tanjung Pulo has similarities with other Umang Caves, and the existing relief carvings provide an ilustration of its fuction. Currently, the Karo people no longer regard The Umang Cave as part of their cultural heritage, but rather view it as an object related to the supernatural being called umang.